EFEKTIVITAS MEDIA PUBLIKASI ONLINE BENTARA BUDAYA BALI (AGENDA BERKALA: SINEMA BENTARA PERIODE JANUARI-MARET 2017) - Siswan Dewi, Ni Made; Purnawan, Ni Luh Ramaswati; Pradipta, Ade Devia (E-Jurnal Medium, 2018)
AB S T RAC T O nly few cultural public spaces that can periodically and continuously organize cultural arts activities, while maintaining and  managing communications with  the  public. As  a  non-profit public space, Bentara Budaya Bali has a public relation that manages publications through various online media. Utilization of online publication media is also an effort of the mission of ’transfer of knowledge’ or the extension of awareness through the knowledge that arranged in such a way in editorial publication. The agenda of Bentara Budaya Bali which utilizes this kind of online publication media is Sinema Bentara.The purpose of this research is to know how the effectiveness of Bentara Budaya Bali online publication media in informing the agenda of Sinema Bentara, and to know which online publication media  is  the  most  effective.  This  type  of  research  is  quantitative  with  a  descriptive  statistical approach. The technique of collecting data of this research is questionnaire to the visitors of Sinema Bentara from January until March 2017.   Keywords: Bentara Budaya Bali, Online Media, Public Relations, Publication, Sinema Bentara